Tradisi Ijazah pada Prosesi Ngabungbang di Pondok Pesantren Cikalama Sumedang dalam Perspektif Filsafat Kebudayaan - Hadziqi, Muhammad Rifqi (Jurnal Riset Agama, 2021)
Traditional ceremonies and traditions that contain values and norms in society, are a form of culture. In the Cikalama community, there is a Ngabungbang tradition. The purpose of this paper is to answer the problems that are the subject of the research: 1) the Ngabungbang Tradition at Pondok Pesantren Cikalama; 2) The procession of the implementation of the Ngabungbang tradition at the Pondok Pesantren Cikalama; and 3) Sutan Takdir Alisjhabana's cultural philosophy analysis of the Ngabungbang tradition at the Pondok Pesantren Cikalama. This research is a field research, with this research is a qualitative descriptive method, and the theory of cultural philosophy of Sutan Takdir Alisjahbana as a knife of analysis. The findings in this research are firstly, Ngabungbang is a tradition to have a good relationship with God, the Prophet, ancestors, as well as with the supernatural powers that he believes in, and is defined as a pilgrimage to the graves of ancestors who contributed to the spread of Islam. Second, the procession of implementing the Ngabungbang tradition is carried out in several stages, namely, reading sholawat and dhikr, listening to advice from the organizers and finally waiting for the prayer to be awarded. Third, the analysis of the dominant values of STA shows that the style/character/character of the culture in the Ngabungbang tradition is an expressive culture.